(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article examines the relationship between the digital economy and online education, as well as their impact on business and consumers. Describes how digital technologies are changing the economic landscape and opening up new opportunities for education. Examples of research in the field of digital economy and online education conducted in Uzbekistan and abroad are considered. Conclusions are given that the development of the digital economy requires highly qualified personnel, and online education is one of the tools for adapting people to new technologies. The conclusion highlights the importance of the relationship between the digital economy and online education for our future. The research methods used were analysis of scientific articles, reports and studies in this area. Literature includes works of world and Uzbek scientists.